Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/pharmaceutics13071014
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Dose Administered to Children Using Off-Labelled or Unlicensed Oral Dosage Forms

Abstract: The pediatric population suffers from a lack of age-appropriate medicines leading to unsafe situations when off-labelled or unlicensed drugs are used. Assessing the best option to administrate medicines when manipulations are required is essential in order to improve child care. This study aimed to compare the accuracy of the administered dose provided by three dosage forms and their techniques of administration. Different techniques of administration were assessed, covering three oral dosage forms (commercial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…We have previously shown that DF modification at the point of administration to achieve the required dose is common in paediatric practice [ 42 ]. However, the safety and risks in terms of dose accuracy and handling associated with this practice are often unknown [ 11 , 12 ]. This study demonstrated that manipulations of medicines used in children are performed for many reasons, including patient preference.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that DF modification at the point of administration to achieve the required dose is common in paediatric practice [ 42 ]. However, the safety and risks in terms of dose accuracy and handling associated with this practice are often unknown [ 11 , 12 ]. This study demonstrated that manipulations of medicines used in children are performed for many reasons, including patient preference.…”
Section: Discussionmentioning
confidence: 99%
“…Many, if not most, of these dose forms provide only “close enough” dosing flexibility for individual patients. However, “close enough” often is not good enough, especially for the most vulnerable of patients [ 9 ]. In our experience, how to measure exact milligram per kilogram (mg/kg) doses from these solid orals in the in-patient setting would be problematic, considering that the pharmacies in most U.S. pediatric institutions provide a measured, ready-to-give liquid dose form for the nurse to administer for improved patient safety.…”
Section: Fda-approved Manufactured Dosage Forms Marketed In the Us Si...mentioning
confidence: 99%
“…A recent literature review aimed to estimate the rates of pediatric off-label and unlicensed drug use [50]. Many studies reported high rates of off-label (up to 78.7%) and unlicensed (up to 35%) drug use in different pediatric patient settings [51]. The lack of clinical safety and efficacy data for the indication and age range, as well as the dose, dosage form and route of administration, places these children at increased risk for adverse events.…”
Section: Impacts Of Off-label and Unlicensed Medication Use In Childrenmentioning
confidence: 99%